ANCAMAN PIDANA MATI TERHADAP PEMBERANTASAN TINDAK PIDANA KORUPSI - Abdul Manan (Unissula, 2020)
This research aims to determine the policy on the formulation of the death penalty against the eradication of corruption and to find out the obstacles and solutions in implementing the death penalty against the eradication of corruption based on the applicable laws in Indonesia. This research method uses an empirical juridical approach. Based on the research findings, it is known that the capital punishment policy can be interpreted as a special maximum criminal sanction in which the level of implementation in Indonesia is difficult to apply because so far capital punishment still reaps pros and cons in its imposition in various criminal cases. no exception in the criminal case of corruption. There are several weaknesses and obstacles in the application of the death penalty in the eradication of the criminal act of corruption, one of which is the death penalty as a burden is only punishable for certain criminal acts of corruption and is not aimed at all forms of corruption. In certain circumstances the most likely juridical reason to occur is in the form of a recidive crime, however it does not contain any rules or definitions (recidive) even though repetition is a juridical technical term.